Metabolic heat generation in larval masses of the black soldier fly, Hermetia illucens L. (Diptera: Stratiomyidae), at different stocking rates - Weldon, Christopher W. (University of Pretoria, 2025)
Dissertation (MSc Agric ( (Entomology))--University of Pretoria, 2025.